Heisenberg and the Nazi atomic bomb project : a study in German culture - Rose, Paul Lawrence (University of California Press, 1998)
Digging deep into the archival record among formerly secret technical reports, Rose examines early thinking about the atomic bomb not only on the German side but also among Allied scientists. He finds that the early history of fission bomb physics had no shortage of false starts and fumbles in both camps. But, whereas the Allied physicists' ideas crystallized into a realistic prospect for a bomb toward the end of 1940. Heisenberg's basic misconceptions persisted, influencing the German leaders not to push for atomic weapons. In fact, Heisenberg never had to face the moral problem of whether he should design an actual bomb for the Nazi regime. Rose's exploration of the German mentality that made it quite reasonable for "unpolitical" scientists to support the regime in power, whatever its form, shows the extent to which Heisenberg and others could devote themselves to research they regarded as patriotic.